Physical Properties of LYSO Scintillator for NN-PET Detectors - Junwei Du; Yonggang Wang; Lijun Zhang; Zhonghui Zhou; Zizhong Xu; Xiaolian Wang (2009 2nd International Conference on Biomedical Engineering and Informatics, 2009)
Cerium doped lutetium oxyorthosilicate scintillators, such as LYSO, which possess high stopping power, high light output and fast decay time, are promising candidates for use in positron emission tomography. In this paper, the luminescence and nuclear spectroscopic properties of two LYSO samples, used in the NN-PET detectors, are studied. UV-excited emission spectra show that maximum emission spectral values are within the range of 400-425 nm, which is well compatible with spectral response of PMT H7546B. The decay time, energy resolution, light output and energy spectra related to coincidence time window were investigated. The decay times of the two LYSO samples are 34.16plusmn1.43ns, 34.26plusmn1.95ns, respectively. The energy resolution and the light output, relative to Nal(Tl), are 10.25%plusmn0.06%, 10.17%plusmn0.10% and 75.3plusmn5.7, 76.1plusmn5.8 respectively when detected with PMT XP2262B. The energy spectra change obviously with coincidence time window and coincidence energy resolution is 14% when obtained using coincidence detector based on LYSO and H7546B.